A cidade da flânerie, do vazio e da errância em Estorvo, de Chico Buarque - Ignácio, Ewerton de Freitas [UNESP] (My University, 2012)
This article aims to perform a reading of Estorvo (1991), by Chico Buarque, trying to show that you have in the work, setting up an urban poetics of emptiness and wandering through the individual unfolded the protagonist wandering dazed and without the right direction, performs on the streets of a big city. In this respect, it is interesting to observe how a fragmented narrative - in whole and in language that conforms - is consistent with the picture of the experience of a character who, in the midst of an urban setting - with brief references to elements of the universe rural - through the experience of mutual incomprehension, violence and the impossibility of a full communication with each other, always in a dazed condition and lost flâneur.
The city for dawdling, emptiness and wandering in Estorvo by Chico Buarque
Keywords: Brazilian contemporary novel; Chico Buarque; Flâneur; Urban experience